Germinação de sementes e sobrevivência de plântulas de Himatanthus sucuuba (Spruce) Wood. em resposta ao alagamento, nas várzeas da Amazônia Central - Ferreira, Cristiane (Acta Amazonica, 2020)
Himatanthus sucuuba is a tree which colonizes the varzeas of Central Amazonia. The present work was carried out in order to analyze the adaptive strategies of the species to cope with the long periods of flooding common in the várzea. Seeds were accompanied from germination until the seedling stage, in experimental conditions simulating natural field conditions (terrestrial phase and flooding period). Germination was tested in two substrates: sand + sawdust (only irrigated), and in water (submergence). The seedlings produced were then subjected, for 120 days, to three treatments: control (daily irrigation), partial submersion (root system) and total submersion (whole seedling). Alterations in the morphology of seedlings and in root anatomy were examined, together with the activity of the enzyme alcohol dehydrogenase (ADH) 0, 15, 30, 60, 90, and 120 days after the start of the treatments. Irrespective of the flooding regime, germination rates and seedling formation were high, both above 80%. Under partial submersion, hypertrophic lenticels, adventitious roots and aerenchyma were formed in the roots while ADH activity remained high until the 60th day of flooding, declining afterwards. Seedlings under total submersion lost all leaves, did not form adventitious roots or lenticels, but developed aerenchyma. These seedlings showed the highest values of ADH, which remained high until the end of the experiment, indicating the diversion of the aerobic metabolism to the production of ethanol as the main pathway to maintain the energetic balance. Although some totally submersed seedlings died, 70% of them survived the 120 days of flooding. Seedlings of H. sucuuba modulate morpho-physiologically the tolerance to flooding according to the time of exposure to the stress and the height of the water column.